Estimation of the Probability of Default of Corporate Borrowers - Rylov, Denis V.; Shkurkin, Dmitry V.; Borisova, Anna A. (International Journal of Economics and Financial Issues, 2016)
Lending to the corporate sector represents a significant part of the activities of the Russian banking sector. At the beginning of 2014 the volume of lending to non-financial organizations amounted to about 56% of the value of the loan portfolio and 39% of the value of Russian banks' assets. Meanwhile, the level of outstanding debt of the corporate loan portfolio tends to increase. A further increase in the share of corporate defaults in the portfolios of banks may cause instability in the banking sector and the financial system as a whole. A large proportion of lending in the Russian market represented lending construction companies. The crises of 2007-2009, 2015-2016 shows that companies in this industry is largely affected by macroeconomic shocks, which leads to interest in the construction of a model / estimation of default probability is for construction industry. In this article we consider one of the approaches to modeling the probability of default of construction companies use logit-models of binary choice on the basis of financial reporting data, institutional characteristics, as well as macroeconomic indicators, as a tool for accounting effect of cyclic economy. Keywords: Probability of default, credit risk, logit model JEL Classifications: E50, L79, G30